Comparison between COVID-19 and DHF co-disease with COVID-19 alone in two pediatric sibling patients - Tatura, Suryadi Nicolaas Napoleon (Indonesian Pediatric Society, 2024)
We report herein the difference between Corona virus disease-19 (COVID-19) and dengue hemorrhagic fever (DHF) co-infection compared with COVID-19 alone in two pediatric sibling patients. This case report highlights a 10-year-old boy with both COVID-19 and DHF who had less severe coagulation disorder than his sister with COVID-19 alone. In a patient with a dual infection, the presence of dengue antibodies may induce immunological protection against COVID-19. We found reports of milder symptoms in patients who had dengue prior to SARS- CoV-2 infection; however, the opposite occured when SARS-CoV-2 infection precedes dengue.